Green awakening: The rising influence of minority shareholders And ESG in shaping China's sustainable future - Shanshan Yue; Norkhairul Hafiz Bajuri; Guang Ye; Farid Ullah (Sustainable Futures, 2025)
This study examines the impact of minority shareholder protection (MSP) on environmental innovation (EI) in China's A-share market, with ESG ratings as a moderating factor. While existing studies often emphasize minority shareholders’ tendency to prioritize short-term gains, we find that MSP positively affects EI performance, using a decade-long panel dataset (2013–2022) comprising 33,718 firm-year observations. Empirical findings also reveal that high ESG ratings can effectively amplify this effect. Specifically, ESG ratings encourage minority shareholders to remain silent no more. Additionally, results using international ESG standards highlight the suitability of local standards for developing countries. Regional analysis reveals heterogeneity in the effectiveness of ESG ratings across China, with the strongest effects observed in the middle region, where ESG ratings act more like a regulatory tool, pushing corporate actions to align with sustainability goals. Two-step GMM estimations further validate the robustness of these results. This study offers three key contributions. First, it expands the understanding of MSP as a driver of sustainability by demonstrating its role in fostering EI, a perspective often overlooked in previous studies. Second, it introduces the novel moderating role of ESG ratings, showing how they can shift minority shareholders’ focus toward long-term sustainability goals. Third, by analyzing regional heterogeneity, this research highlights the unique dynamics of ESG effectiveness in transitional economies like China. Integrating stakeholder and signaling theories, this study underscores the transformative potential of combining robust MSP mechanisms with credible ESG signals for achieving sustainable innovation.